Prognostic value of neutrophil gelatinase-associated lipocalin in acute heart failure - Alvelos, M (2013)
Background: The identification of patients at risk for worse outcome is still a challenge. We hypothesized that cystatin C, a marker of renal function, and neutrophil gelatinase-associated lipocalin (NGAL), a marker of acute renal injury, would have a role in the prognostic stratification of these patients. Methods: We prospectively evaluated 121 patients admitted for acute HF. Serum NGAL and cystatin C levels were measured on the first morning after admission. The outcome measures used were the occurrence of death from all causes, and the combined endpoint defined as the first occurrence of either death or hospital admission. Patients were followed for up to 3 months. Results: The variables associated with a higher occurrence of death in a univariate approach were older age and higher levels of BNP, cystatin C and NGAL, and those associated with the occurrence of the combined endpoint were older age, Diabetes mellitus, lower GFR, type 1 cardio-renal syndrome, BNP, cystatin C and NGAL. BNP and NGAL remained independent predictors of the occurrence of both all-cause death and the combined endpoint. NGAL levels in the 75th percentile (> 167.5 ng/mL) were associated with a 2.7-fold increase in the risk of death and a 2.9-fold increase in the risk of the first occurrence of either death or hospitalization. Conclusions: Serum NGAL, a marker of acute renal injury, is an independent predictor of worse short term prognosis in patients with acute HF. This suggests a role of renal damage, apart from renal function, in the prognosis of these patients.